Millionaires Please Apply Morphoses 2008 - Parry, Jann 1927-2008 (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Christopher Wheeldon's Morphoses company has accomplished its second autumn tour, presenting brief seasons in Vail, London and New York.